2017 Canadian Association of Gastroenterology Educational Needs Assessment Report. Issue 1 (8th February 2018) - Waschke, Kevin A; Sparkes, Karen
Abstract: The annual survey of Canadian Association of Gastroenterology (CAG) members' educational needs was conducted via an online survey sent to 772 CAG members in March 2017. A total of 211 individuals responded to the survey, of which 197 went on to rate educational topics. Similar to previous years, endoscopy techniques, Crohn's & Ulcerative Colitis, and Inflammatory Bowel Disease (IBD) topics were most in demand for future educational events. Other highly rated areas were celiac disease, functional bowel disorders (IBS), GI oncology, non-IBD intestinal disorders, upper GI bleeding, nutrition, NAFLD, and chronic diarrhea.